Defining a research agenda for youth sport specialisation in the USA: the AMSSM Youth Early Sport Specialization Summit. Issue 3 (18th January 2021) - Kliethermes, Stephanie A; Marshall, Stephen W; LaBella, Cynthia R; Watson, Andrew M; Brenner, Joel S; Nagle, Kyle B; Jayanthi, Neeru; Brooks, M Alison; Tenforde, Adam S; Herman, Daniel C; DiFiori, John P; Beutler, Anthony I
Abstract : Sport specialisation is becoming increasingly common among youth and adolescent athletes in the USA and many have raised concern about this trend. Although research on sport specialisation has grown significantly, numerous pressing questions remain pertaining to short-term and long-term effects of specialisation on the health and well-being of youth, including the increased risk of overuse injury and burnout. Many current elite athletes did not specialise at an early age. Methodological and study design limitations impact the quality of current literature, and researchers need to prioritise pressing research questions to promote safe and healthy youth sport participation. The American Medical Society for Sports Medicine hosted a Youth Early Sport Specialization Summit in April 2019 with the goal of synthesising and reviewing current scientific knowledge and developing a research agenda to guide future research in the field based on the identified gaps in knowledge. This statement provides a broad summary of the existing literature, gaps and limitations in current evidence and identifies key research priorities to help guide researchers conducting research on youth sport specialisation. Our goals are to help improve the quality and relevance of research on youth sport specialisation and to ultimately assure that opportunities for healthy and safe sport participation continue for all youth.